PENGARUH TIPE INDUSTRI, UKURAN PERUSAHAAN, DAN PROFITABILITAS TERHADAP CORPORATE SOCIAL RESPONSIBILITY PADA PERUSAHAAN YANG TERDAFTAR DI BEI TAHUN 2016-2018 - Akhmada Faidah; M. Cholid Mawardi; Siti Aminah Anwar (Universitas Islam Malang, 2020)
ABSTRACTThis study aims to analyze the influence of industry type, company size, and profitability on social responsibility in manufacturing companies listed on the Stock Exchange in 2016-2018. Data collection uses a purposive sampling method for manufacturing companies listed on the Indonesia Stock Exchange in 2016-2018. There are 50 companies used as research samples. Hypothesis testing is done by multiple regression analysis. This study uses independent variables such as: industry type, company size, profitability; and the dependent variable used is corporate social responsibility. The results of the regression model show simultaneously the type of industry, company size and profitability affect corporate social responsibility. while partially the type of industry and profitability affect corporate social responsibility, but the size of the company does not affect corporate social responsibility.Keywords: corporate social responsibility, industry type, company size, profitability.